Comparative lipid profiling of murine and human atherosclerotic plaques using high-resolution MALDI MSI - Khamehgir-Silz, Pegah; Gerbig, Stefanie; Volk, Nadine; Schulz, Sabine; Spengler, Bernhard; Hecker, Markus; Wagner, Andreas H. (Pflügers Archiv, 2022)
The distribution of atherosclerotic lesions in the aorta and its branches of ApoE knockout (ApoE−/−) mice is like that of patients with atherosclerosis. By using high-resolution MALDI mass spectrometry imaging (MSI), we aimed at characterizing universally applicable physiological biomarkers by comparing the murine lipid marker profile with that of human atherosclerotic arteries. Therefore, the aorta or carotid artery of male ApoE−/− mice at different ages, human arteries with documented atherosclerotic changes originated from amputated limbs, and corresponding controls were analysed. Obtained data were subjected to multivariate statistical analysis to identify potential biomarkers. Thirty-one m/z values corresponding to individual lipid species of cholesterol esters, lysophosphatidylcholines, lysophosphatidylethanolamines, and cholesterol derivatives were found to be specific in aortic atherosclerotic plaques of old ApoE−/− mice. The lipid composition at related vessel positions of young ApoE−/− mice was more comparable with wild-type mice. Twenty-six m/z values of the murine lipid markers were found in human atherosclerotic peripheral arteries but also control vessels and showed a more patient-dependent diverse distribution. Extensive data analysis without marker preselection based on mouse data revealed lysophosphatidylcholine and glucosylated cholesterol species, the latter not being detected in the murine atherosclerotic tissue, as specific potential novel human atherosclerotic vessel markers. Despite the heterogeneous lipid profile of atherosclerotic peripheral arteries derived from human patients, we identified lipids specifically colocalized to atherosclerotic human tissue and plaques in ApoE−/− mice. These data highlight species-dependent differences in lipid profiles between peripheral artery disease and aortic atherosclerosis.
Online veröffentlicht: 19. November 2021
Gesehen am 20.02.2023